KODE ETIK PSIKOLOGI DALAM MENDAPATKAN ILMU YANG BERMANFA’AT - Nur Syarifuddin (CENDEKIA: Jurnal Studi Keislaman, 2017)
The human’s fallecy of thinking, mental and actions today is spreading in entire the world. Muslim Families have been poisoned by secular thought, so they are far from the true understanding of Islam. They have achieved academic degrees, social titles, and social status in society, but they do not make them feel fear of God and the more correct the attitude of worship to Him, even to the contrary. This is caused when looking for knowledge, there are some things that are not true, they do not understand the code of ethics or adab-adab to seek a knowledge and how to achieve or get a useful science. Then the next educator in the view of Islam is a teacher or lecturer. Simply put, teachers can be called as teachers and educators at once. The code of ethics is a set of values ​​to be adhered to and executed as well as possible in the performance of something. While psychology is a science that focuses on the behavior and mental processes that lie behind, as well as application in human life. A useful science is the science which can make the owner to be closer to God, not necessarily what it is with the knowledge we have gained but the extent of our devotion and servitude to the Khaliq with the knowledge we gain. In this article we will discuss about the code of ethics of psychology in obtaining the “manfa'at” science, with the meaning of psychology here refers to the psychology or personality of a person in the search for knowledge, as well as the personality of the teacher or educator as a supplier of knowledge to obtain benefit.